Working Capital Management Efficiency of Cement Sector of Pakistan - Talat Afza (Journal of Economics and Behavioral Studies, 2011)
The corporate finance literature has traditionally focused on the study of long-term financial decisions. Researchers have particularly examined investments, capital structure, dividends or company valuation decisions, among other topics. However, short-term assets and liabilities are important components of total assets and needs to be carefully analyzed. Management of these short-term assets and liabilities warrants a careful investigation since the working capital management plays an important role for the firm’s profitability and risk as well as its value. It requires continuous management to maintain proper level in various components of working capital i.e. cash, receivables, inventory and payables etc. The present study is an attempt to evaluate the efficiency of the working capital management of cement sector of Pakistan for the period 1988-2008. Instead of employing the traditional ratios; working capital efficiency has been measured in terms of utilization index, performance index and total efficiency index as suggested by Bhattacharya (1997). This paper also tests the speed of achieving the target level of efficiency by an individual firm during the period of study using industry norms as the target level of efficiency. Findings of the study indicate that the cement sector as a whole did perform well during the study period.